Unanticipated Consequences of Switching to Sugammadex: Anesthesia Provider Survey on the Hormone Contraceptive Drug Interaction. Issue 3 (24th September 2022) - Dwan, R.L.; Raymond, B.L.; Richardson, M.G.
Abstract : ( Anesth Analg . 2021;133:958–966) Sugammadex is thought to reduce the efficacy of hormonal contraceptive (HC) due to its ability to bind progesterone. In February 2017, a large, tertiary-care medical center switched from neostigmine to sugammadex as the neuromuscular blockade (NMB) drug of choice. Care should be taken by anesthesiologists to recommend alternative contraceptive methods for patients exposed to sugammadex to avoid unintentional pregnancy. This study, conducted 2 years following the switch to sugammadex, aims to assess the institution's anesthesiologist provider management of the drug and any knowledge gaps present.